2015
DOI: 10.1590/0100-2945-024/14
|View full text |Cite
|
Sign up to set email alerts
|

Adubação N-K No Abacaxizeiro ‘Brs Imperial’ – Ii Efeito No Solo, Na Nutrição Da Planta E Na Produção

Abstract: RESUMO-o abacaxizeiro 'BRS imperial' é uma cultivar resistente à fusariose, apresenta frutos saborosos, mas ainda é pouco conhecido dos fruticultores. este trabalho teve como objetivo avaliar o efeito de diferentes doses de n e K nas características químicas do solo, nos teores foliares de nutrientes e nas variáveis de produção de um cultivo de 'BRS imperial'. o experimento foi instalado no espaçamento 0,90 x 0,40 x 0,40 m, com quatro doses de n (0; 160; 320 e 550 kg ha NK FERTILIZATION IN 'BRS IMPERIAL' PINE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The comparative nutritional behavior among the cultivars is not described in the literature. The values found in this study agree with several studies for the cultivation of pineapple seedlings, except for calcium content (Prado et al [ [20]) and lower than those found by [4].…”
Section: Resultssupporting
confidence: 92%
“…The comparative nutritional behavior among the cultivars is not described in the literature. The values found in this study agree with several studies for the cultivation of pineapple seedlings, except for calcium content (Prado et al [ [20]) and lower than those found by [4].…”
Section: Resultssupporting
confidence: 92%
“…Imperial. Oliveira et al (2015c) working with the same cv., reported an estimated yield of 42 t ha -1 and fruit weight with and without crown of 1086 g and 967 g, respectively, at the maximum physical doses of 365 and 374 kg ha -1 of N. For Pineapple Gold, the expression of maximum capacity according to Guarçoni & Ventura (2011), yields of 650.6 and 735.9 kg ha -1 of N and K 2 O, respectively, with yield of 65.4 t ha -1 were obtained.…”
Section: /9mentioning
confidence: 99%
“…Correlation in statistics is a widely used tool since it allows the quantitative evaluation of the relevance of one characteristic in relation to the other. Oliveira et al (2015), when studying the Pearson's correlation coefficients in the production characteristics of the 'BRS Imperial' pineapple, reported that the significant negative correlation with a higher coefficient of correlation (-0.77) indicates the possibility that the length of the fruit exerts a greater influence on the smallest crown mass than the diameter (-0.45) and mass of the fruit (-0.56). In other words, they concluded that the larger the mass of the fruit, the greater its diameter and length, and the smaller the crown.…”
Section: Introductionmentioning
confidence: 99%